2022
DOI: 10.3390/biom12030436
|View full text |Cite
|
Sign up to set email alerts
|

Neurons with Cat’s Eyes: A Synthetic Strain of α-Synuclein Fibrils Seeding Neuronal Intranuclear Inclusions

Abstract: The distinct neuropathological features of the different α-Synucleinopathies, as well as the diversity of the α-Synuclein (α-Syn) intracellular inclusion bodies observed in post mortem brain sections, are thought to reflect the strain diversity characterizing invasive α-Syn amyloids. However, this “one strain, one disease” view is still hypothetical, and to date, a possible disease-specific contribution of non-amyloid factors has not been ruled out. In Multiple System Atrophy (MSA), the buildup of α-Syn inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…Cell cultures expressing aSyn tagged with a nuclear localization signal develop pSyn-positive nuclear inclusions, and this aggregation is not caused by the localization signal [ 16 ]. Primary neuron cultures treated with fibrils formed from copper-exposed aSyn showed increased nuclear inclusions, which is consistent with mouse data that indicate that specific aSyn strains have a greater propensity for nuclear aggregation [ 28 , 30 ]. Following neurotoxin exposure, apoptotic cells in culture increase their nuclear aSyn and exhibit nuclear aSyn aggregation [ 31 ].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cell cultures expressing aSyn tagged with a nuclear localization signal develop pSyn-positive nuclear inclusions, and this aggregation is not caused by the localization signal [ 16 ]. Primary neuron cultures treated with fibrils formed from copper-exposed aSyn showed increased nuclear inclusions, which is consistent with mouse data that indicate that specific aSyn strains have a greater propensity for nuclear aggregation [ 28 , 30 ]. Following neurotoxin exposure, apoptotic cells in culture increase their nuclear aSyn and exhibit nuclear aSyn aggregation [ 31 ].…”
Section: Introductionsupporting
confidence: 88%
“…Additionally, wildtype mice that received a gastric wall PFF injection displayed nuclear inclusions [ 27 ]. The formation of nuclear inclusions increases when specific aSyn PFF strains are used or if toxin insults, such as MPTP exposure, are combined with PFF injection [ 28 , 29 ]. In vitro models can also display nuclear inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Demonstration remains, therefore, to be provided in a model of fibrillar formation, possibly using specific preformed fibrils inducing a pathology clearly reminiscent of MSA. 16 Our results pave the way for a more comprehensive analysis of the role of GRK2 in MSA. The metabolic role of GRK2 in insulin resistance and associated conditions receives much attention.…”
Section: Discussionmentioning
confidence: 67%
“…We recently showed that S129‐phosphorylated α‐syn corresponds to the accumulation of phosphorylated α‐syn monomers/oligomers and not to the appearance of the distinctive fibrillar α‐syn aggregates that are present in the brains of MSA or PD patients 15 . Demonstration remains, therefore, to be provided in a model of fibrillar formation, possibly using specific preformed fibrils inducing a pathology clearly reminiscent of MSA 16 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, distinct αS species translocate from the nucleus to neuronal processes during neuronal differentiation, which suggests that the maturation process of the nervous system may affect subcellular localization [ 59 ]. With respect to protein conformational change and aggregation, exposure to human fibrotic αS seed facilitates the formation of intranuclear inclusions in mouse primary cortical neurons [ 60 ]. Furthermore, the inoculation of αS preformed fibrils into the stomach wall of wild-type mice resulted in the formation of a small number of nuclear inclusions in the dorsal motor nucleus of the vagal nerve [ 61 ].…”
Section: Interaction Between αS and Epigenetic Factorsmentioning
confidence: 99%